Views and perceptions of the public toward COVID-19 vaccine in Saudi Arabia - Abrar K. Thabit; Aisha F. Badr; Lama Jad; Jimmy Jose; Susanne Kaae; Ramune Jacobsen; Ghuna Al-Saudi (Elsevier, 2023)
Background: Numerous surveys studied individuals' decision to receive COVID-19 vaccine but the motives behind accepting or refusing COVID-19 vaccines are not yet fully understood. We aimed to more qualitatively explore the views and perceptions toward COVID-19 vaccines in Saudi Arabia to provide recommendations to mitigate the vaccine hesitancy issue. Methods: Open-ended interviews were conducted between October 2021-January 2022. The interview guide included questions about beliefs in vaccine efficacy and safety, and previous vaccination history. The interviews were audio-recorded, transcribed verbatim, and the content was analyzed using thematic analysis. Nineteen participants were interviewed. Results: All of the interviewees were vaccine acceptors; however, three participants were hesitant as they felt they were forced to receive it. Several themes emerged as the reasons to accept or refuse the vaccine. The key reasons behind vaccine acceptance were the sense of obligation to fulfill a governmental command, trust in the government decisions, vaccine availability, and the impact of family/friends. The main reason behind vaccine hesitancy was doubts regarding vaccine efficacy and safety and that vaccines were pre-invented, and the pandemic is made-up. Participants' sources of information included social media, official authorities, and family/friends. Conclusion: Findings from this study show that the convenience of receiving the vaccine, the abundance of credible information from the Saudi authorities, and the positive influence of family/friends were among the major factors that encouraged the public in Saudi Arabia to get vaccinated against COVID-19. Such results may inform future policies regarding encouraging the public to receive vaccines in cases of pandemic.